Heutagogy in Improving Metacognitive Intelligence of Students in Pesantren - M. Yunus Abu Bakar; Hasan Baharun; Nur Silfiataun Hasanah (Journal An-Nafs: Kajian Penelitian Psikologi, 2022)
This study aims to analyze the heutagogical approach to improving the metacognitive intelligence of students at Ma'had Aly. This study used a qualitative approach with phenomenological research. The researchers attempted to understand the phenomena of education and learning activities in Ma'had Aly. Researchers conducted participatory observations, interviews, and documentation. Data analysis was carried out through the stages of data display, data reduction, and data conclusion. The results showed that the heutagogical approach implemented at Ma'had Aly improved students' metacognitive intelligence through some activities, including a reading test with the blank matter, meaning understanding, memorizing nadzom, and achieving the learning goal.